Bases of inorganic and organic chemistry - Ved, M.; Alami, D.; Slavkova, M. (Національний технічний університет "Харківський політехнічний інститут", 2016)
Stated fundamental theoretical principles of general, inorganic and organic chemistry and analyzed the reactivity of the most important classes of inorganic and organic substances. A multivariate tasks and exercises for classroom and independent work are proposed. For university students full-time and distance learning areas "Chemical Technology and Engineering" "Oil and gas engineering and technology" and others.
Keywords: textbook; inorganic chemistry; atomic structure; periodic table; chemical bonding; covalent bond models; ionic bond models; chemical thermodynamics; chemical kinetics; solution chemistry; electrochemical processes; electrochemical systems; corrosion of metals; organic chemistry; alkanes; cycloalkanes; alkyl halides; unsaturated hydrocarbons; aromatic hydrocarbons; derivatives hydrocarbons; alcohol; ethers; phenols; aldehydes; ketones; carboxylic acids; derivatives; amines; IUPAC nomenclature rules; organic compounds